Progressive System Sclerosis - A Case Report - Jyothi S Kumar; L Ashok; G P Mamatha (Wolters Kluwer Medknow Publications, 2003)
Progressive systemic sclerosis is a disease that involves connective tissues and.blood vessels leading to fibrosis. The skin as well as internal organs are involved. A case of progressive systemic sclerosis is presented and review of literature concerning oral manifestations of this condition is presented.